Thermal Properties Evaluation of Pavement Mixture: A Review - ahmad shukri, muhammad syazwan; Mohd Kamaruddin, Nurul Hidayah (Recent Trends in Civil Engineering and Built Environment, 2021)
Asphalt mixture is generally a temperature-sensitive material. The mechanical properties and efficiency of this asphalt mixture can often change significantly with temperature. It is necessary to use the elevated temperature to dry the aggregate, coat them with asphalt binder and achieved the desired workability. Despite of that, climatic factor is the biggest problem for asphalt binder. The aim of this study is to conduct a simple literature review on the thermal properties evaluation of pavement mixture. The literature search used repositories database (ScienceDirect, Google Scholar, Scopus, Google) and have identified in 13 articles. Based on the review, there are various method have been used to measure the thermal properties of pavement mixture. The factor such as density and additive in asphalt binder can give effect on the thermal conductivity and specific heat capacity.